Qualitative investigations on the stability of Al2O3-SiO2 hybrid water-based nanofluids. Issue 1 (April 2020) - Ismail, H; Sulaiman, M Z; Aizzat, M A H
Abstract: Qualitative experiments were carried out to investigate the stability of Al2 O3 -SiO2 hybrid water-based nanofluids. The main nanoparticles used in this work were Al2 O3 and SiO2 since these types of nanoparticles has been widely used and proposed in many applications and information on their hybrid dispersion stability characteristic are still elusive. The present work demonstrated the stability of Al2 O3 -SiO2 hybrid nanofluids using various preparation techniques and successively elucidating the optimum preparation method for hybrid nanofluid. The hybrid water-based nanofluid were prepared by dispersing a 50:50 ratio of Al2 O3 -SiO2 nanoparticles into distilled water to achieve total volume concentration of C =0.001, 0.01 and 0.1 vol%. Successively, the hybrid nanofluids were prepared using magnetic stirrer and ultrasonic bath. The samples are categorised into five preparation method which are: (i) 1 hour sonication, (ii) 1 hour magnetic stirrer, (iii) 0.25 hour magnetic stirrer and 1 hour sonication, and (iv) 0.5 hour magnetic stirrer and 1 hour sonication and (v) without magnetic stirring and sonication. The height of sedimentation and colloidal stability of each preparation methods were observed in the duration of 2 weeks. In the present work, it was observed that the dispersion stability of hybrid nanofluids prepared by applying magnetic stirrer for 15 minutes with prior to 1 hour of sonication had demonstrated the highest stability indicated by the lowest height of sedimentation and high colloidal stability.